A natural laboratory to elucidate the evolution of endogenous‐exogenous retroviral interactions. Issue 11 (19th March 2021) - Chiu, Elliott S.; Gagne, Roderick B.
Abstract : The advent of whole genome sequencing has revealed much about the genomes of animals including the relatively large percentage of the genome consisting of endogenous retroviruses (ERV; International Human Genome Sequencing Consortium, 2001). An ERV arises when a retrovirus integrates into a host germ cell genome through normal infection processes. Germline infections can be transmitted to offspring through Mendelian inheritance and at times become fixed elements of the host genome (Weiss, 2006). At their inception, these endogenized retroviruses maintain all the functions of their exogenous progenitors and can produce infectious virus (Figure 1). Mutations in the ERV randomly accumulate over time and can lead to the loss of the deleterious effects. In addition, the ERV can provide benefits to the host often via limiting exogenous viral infections (Chiu and VandeWoude, 2020a). However, most of these endogenous viruses are evolutionary relics representing historical infections and have no contemporary exogenous virus. This limits the opportunities to understand the evolution of ERVs and their interactions with exogenous viruses. In this issue of Molecular Ecology, Quigley et al. (2020) use a novel approach to show that koala retrovirus (KoRV) is undergoing endogenization along a geographic gradient with a variety of exogenous variants dispersed across the landscape. This system provides an opportunity to further elucidate the complex mechanisms in which endogenous and exogenous viruses interact and follow the evolution of an ERV in real time.